An Overview on Recent Progress of the Hydrogels: From Material Resources, Properties, to Functional Applications - Wang, Ben‐Xin; Xu, Wei; Yang, Zhuchuang; Wu, Yangkuan; Pi, Fuwei (Macromolecular rapid communications., 2022)
Hydrogels, as the most typical elastomer materials with three‐dimensional (3D) network structures, have attracted wide attention owing to their outstanding features in fields of sensitive stimulus response, low surface friction coefficient, good flexibility, and bio‐compatibility. Because of numerous fresh polymer materials (or polymerization monomers), hydrogels with various structure diversities and excellent properties are emerging, and the development of hydrogels is very vigorous over the past decade. This review focuses on state‐of‐the‐art advances, systematically reviews the recent progress on construction of novel hydrogels utilized several kinds of typical polymerization monomers, and explores the main chemical and physical cross‐linking methods to develop the diversity of hydrogels. Following the aspects mentioned above, the classification and emerging applications of hydrogels, such as pH response, ionic response, electrical response, thermal response, biomolecular response, and gas response, are extensively summarized. Finally, this review is done with the promises and challenges for the future evolution of hydrogels and their biological applications. Hydrogels with 3D network structures have attracted wide attention. This review focuses on state‐of‐the‐art advances, systematically reviews recent progress on construction of hydrogels, and explore three main cross‐linking methods to develop diversities of hydrogels. The classification and emerging applications of hydrogels are extensively summarized, and promises and challenges for the future evolution of hydrogels are discussed.